Clinical academic radiographers – A challenging but rewarding career. (October 2021) - Simcock, I.C.; Reeve, R.; Burnett, C.; Costigan, C.; McNair, H.; Robinson, C.; Arthurs, O.J.
Abstract: Objectives: To explain what a clinical academic career can be, what it can lead to for the individual, profession and most importantly the patient, and why these roles are so important to radiography. Key findings: Multiple challenges to the adoption of clinical academic careers exist, including achievable measurable outcomes, visibility & senior support, and balancing different time demands. Equally the rewards are wide ranging and can advance both the individual and profession through role extension opportunities, increased career progression, patient benefits, and academic and research skills. Conclusion: Clinical academic careers can provide advantages for the individual, department, profession and most importantly the patient with advanced clinical practice through evidenced based research. Implications for practice: Improving clinical academic careers within Radiography will promote research participation and increase radiographic roles in patient-centred research delivery and development. Combining evidenced based research with academic skills will lead to improved patient care and better clinical outcomes. Graphical abstract: Image 1